NUTRITIONAL IMPROVEMENT INTERVENTIONS FOR MALNOURISHED PRESCHOOL CHILDREN: A SYSTEMATIC REVIEW - Dewi Aminah; Anisah Ardiana; Iis Rahmawati (UPT Penerbitan Universitas Jember, 2023)
Background: Feeding difficulties in children can lead to malnutrition. Parents need to measure their toddler's weight regularly every month so they can find out their child's growth. The nutritional quality of children is strongly influenced by their diet and physical activity. The impact of nutritional problems on children does not only affect childhood and adulthood. The purpose of this literature review is to analyze interventions to improve preschool nutrition to optimize their nutritional status. Methods: The research method is a literature review using two electronic databases, namely PubMed and Google Scholar. Results: The total number of titles taken from PubMed and Google Scholar is 137,064. From this study, only 5 articles met the inclusion criteria. This article discusses increasing the knowledge, attitudes and practices of parents, caregivers in child care and teachers in early childhood education in providing balanced nutrition to children by increasing their intake of eating fruits and vegetables and increasing children's motor development by increasing physical activity. Conclusion: the nutritional status of preschool-age children is strongly influenced by the active role of parents, caregivers in child care, and teachers in PAUD related to patterns of providing healthy and balanced nutrition. As well as paying attention to the level of physical activity of children in monitoring children's motor development.